The Infulence of Product Quality, Brand Image and Payment Methods on The Decision to Purchase Wardah Cosmetics at Yaraoutlett Shop - Doni Tresna; Dian Septiana Sari (Utan Kayu Publishing, 2025)
This study aims to determine how much influence product quality, brand image and payment methods have on purchasing decisions at Yaraoutlett Stores located in Binjai City. The data analysis technique uses multiple linear regression, with the help of SPSS software version 26. The number of samples in this study were 79 respondents who were consumers of Wardah products at the Yaraoutlett Store. The test results on product quality have a positive and significant effect partially on purchasing decisions. The test results on brand image have a partially negative and significant effect on purchasing decisions. The test results on payment methods have a positive and partially significant effect on purchasing decisions. The test results simultaneously show that product quality, brand image and payment methods have a positive and significant effect simultaneously on purchasing decisions. The R2 test results amounted to 41% of purchasing decisions which can be explained by product quality, brand image and payment methods. While the remaining 59% is explained by other factors outside the research model. Thus, improving product quality, brand image and more innovative payment methods can be a driving factor in increasing consumer purchasing decisions for Wardah products at Yaraoutlett Stores.